Private sector’s role in agricultural transformation in Africa: Overview - Reardon, Thomas; Awokuse, Titus; Haggblade, Steven; Minten, Bart; Vos, Rob (Alliance for a Green Revolution in Africa, 2019)
Small-scale farms that sell to urban markets in Africa are about 10 times more likely to use fertilizer, manure, and improved seeds, and to invest in soil conservation and “sustainable intensification” than farmers who do not sell to markets (Reardon, Crawford, Kelly, & Diagana, 1995). Farms that undertake those investments tend to have higher yields. Thus, those farms have more output and higher farm income, which in turn provides multiplier effects, generating broader-based rural and urban income, and employment growth (Haggblade, Hazell, & Dorosh, 2007; Reardon, 1997). Adjognon, Liverpool-Tasie, and Reardon (2017) further show that income from rural non-farm employment is, by far, the most important funding source for input purchases in Africa. Dynamic and inclusive agricultural transformation depends on whether smallscale farms are “sandwiched” between (small and medium enterprise (SME)-driven output and input value chains. With the motivation to address those gaps, this Africa Agriculture Status Report (AASR) focuses on the role of the private sector in the output and input value chains in sub-Saharan Africa. We examine its structure, conduct, and performance, particularly in regard to its interface with small farms.